Pedestrian Motor Vehicle Accidents and Fatalities in Botswana-An Epidemiological Study - Mphela, Thuso; Mokoka, Thamani; Dithole, Kefalotse (Frontiers in Sustainable Cities, 2021)
According to WHO, more than 300,000 pedestrian deaths were recorded globally, accounting for 22% of total road user fatalities in 2019. In 2017, Botswana pedestrian fatalities were considerably high at 32% of the total road accident fatalities recorded. This paper investigated causes, distribution, risk and offers potential solutions to pedestrian accidents and fatalities in Botswana. Secondary data extracted from different sources were analyzed through descriptive statistics and stepwise regression modeling was performed to determine significant explanators of pedestrian fatalities. The results show that the “car” vehicle type is responsible for 55% of pedestrian collisions. There is a higher chance of pedestrian fatality when collision is with a lorry with a trailer. On the other hand, driver negligence is also blamed for 55% of pedestrian accidents. Ninety percent (90%) of pedestrian fatalities happen away from road junctions. Truck, fuel imports and nighttime accidents were identified as significant regressors for pedestrian fatalities. Overall, pedestrians are six times more likely to perish in a collision than their counterparts. Adopting sustainable road infrastructure patterns that promote pedestrian safety will foster mode split. Improving road lighting and infusing pedestrian safety into driver training curriculum, while strengthening road traffic law enforcement, will lead to improved pedestrian safety. Future studies should disaggregate pedestrian safety analysis to account for location-specific variations.